Cardiac Surgery in Germany during 2013: A Report on Behalf of the German Society for Thoracic and Cardiovascular Surgery - Funkat, A.; Beckmann, A.; Lewandowski, J.; Frie, M.; Ernst, M.; Schiller, W.; Gummert, J. F.; Cremer, J. (The Thoracic and Cardiovascular Surgeon, 2014)
On the basis of a voluntary registry of the German Society for Thoracic and Cardiovascular Surgery (GSTCVS), data of all cardiac surgical procedures performed in 79 German cardiac surgical units during the year 2013 are presented. In 2013, a total of 99,128 cardiac surgical procedures (implantable cardioverter defibrillator [ICD] and pacemaker procedures excluded) were submitted to the registry. More than 13.8% of the patients were older than 80 years, which remains equal in comparison to the previous year. In-hospital mortality in 40,410 isolated coronary artery bypass grafting procedures (84.5% on-pump and 15.5% off-pump) was 2.9%. In 29,672 isolated valve procedures (including 7,722 catheter-based procedures), an in-hospital mortality of 4.7% was observed. This long-lasting registry of the GSTCVS will continue to be an important tool for quality control and voluntary public reporting by illustrating current facts and developments of cardiac surgery in Germany.
Keywords: cardiac surgery; outcome; registry; congenital heart disease; aortic surgery; organ transplantation